1991
DOI: 10.1144/gsl.sp.1991.058.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Benthos communities in oxygen deficient shelf and upper slope areas of the Peruvian and Chilean Pacific coast, and changes caused by El Niño

Abstract: Besides a well oxygenated shallow water area characterized by an extremely rich benthic life, most of the Peruvian and Chilean continental shelf and upper slope lies within an oxygen minimum zone (omz), the poor macrobenthic colonization of which is in striking contrast to the abundant pelagic life in the overlying waters. However, the eukaryotic benthos in this zone shares the seafloor with an important prokaryotic component of filamentous (‘sphagetti’) bacteria belonging mainly to the genus Thiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 27 publications
1
67
0
2
Order By: Relevance
“…The polychaete Paraprionospio pinnata and the mollusc Nassarius gayi were the most dominant species. Our results are in accordance with previous studies for the upwelling systems of the Peruvian (Tarazona 1984;Tarazona et al 1985Tarazona et al , 1988aTarazona et al , 1996Arntz et al 1991;Yupanqui et al 2007) and Chilean coast in the HCS affected by EN (Gallardo 1985;Gutiérrez et al 2000;Laudien et al 2007).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The polychaete Paraprionospio pinnata and the mollusc Nassarius gayi were the most dominant species. Our results are in accordance with previous studies for the upwelling systems of the Peruvian (Tarazona 1984;Tarazona et al 1985Tarazona et al , 1988aTarazona et al , 1996Arntz et al 1991;Yupanqui et al 2007) and Chilean coast in the HCS affected by EN (Gallardo 1985;Gutiérrez et al 2000;Laudien et al 2007).…”
Section: Discussionsupporting
confidence: 94%
“…Positive effects of EN events on macrozoobenthos communities have been previously reported for the upwelling systems along the Peruvian coast (Tarazona 1984;Tarazona et al 1985Tarazona et al , 1988aTarazona et al , 1996Arntz et al 1991;Arntz and Fahrbach 1996; but see Yupanqui et al 2007), north (Laudien et al 2007) and central Chile (Gallardo 1985;Gutiérrez et al 2000), and were generally suggested to be related with increased water temperature and dissolved oxygen during EN. However, as far as we are aware, no previous studies had reported the potential of this oceanographic anomaly to affect species assembling processes in marine benthic communities.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations